2020
DOI: 10.1186/s12199-020-00858-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in smoking behavior among victims after the great East Japan earthquake and tsunami

Abstract: Background: In areas affected by the tsunami of the great East Japan Earthquake, smoking behavior may have deteriorated due to high stress and drastic changes in living environment. Surveys were conducted to reveal changes in smoking behaviors among victims. Methods: A population-based random-sample home-visit interview survey of victims in Iwate and Miyagi Prefectures affected by the tsunami disaster was conducted in 2012 (n = 1978), while a population-based nationwide survey was conducted in 2013 (n = 1082).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In December 2019, the first cases of a novel coronavirus disease (COVID- 19) were reported in Wuhan, Hubei province, China [1]. The disease quickly spread and has become a pandemic, with over 81 million cases and 1.7 million deaths worldwide as of December 28, 2020 [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In December 2019, the first cases of a novel coronavirus disease (COVID- 19) were reported in Wuhan, Hubei province, China [1]. The disease quickly spread and has become a pandemic, with over 81 million cases and 1.7 million deaths worldwide as of December 28, 2020 [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the threat of COVID-19 could result in negative consequences such as increased tobacco use, or users could have a renewed interest in quitting as a proactive step to improve their health. Historically, other national disasters have resulted in relapse in former smokers or increase in smoking among current smokers [ 18 , 19 , 20 , 21 ]. Additionally, evidence suggests an increased interest in cessation assistance among smokers after experiencing natural disasters [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several cross-sectional studies have shown that perceived stress leads to increased rates of cigarette smoking [1,2]. Multiple reports have also shown that the prevalence of tobacco use increased after anthropogenic and natural disasters, such as the 11 September 2001 attacks [3], Hurricane Katrina [4], and the Japanese tsunami in 2011 [5], where rates of tobacco use in survivors were near double the national averages. The COVID-19 pandemic is the most recent global disaster, with over 250 million infections and 5 million deaths worldwide as of 9 November 2021 [6].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic led to significant changes in lifestyles (e.g., virtual learning, social distancing, and remote working) and economic instability, which resulted in stress, anxiety, and isolation for many people. As the association between negative affect and smoking suggests [ 1 , 2 ], people tend to increase tobacco consumption following the exposure to stressful events, such as natural and human-made disasters [ 3 , 4 , 5 , 6 ]. The COVID-19 pandemic, however, is different from those disasters because of its direct and nationwide impact on the health of all individuals.…”
Section: Introductionmentioning
confidence: 99%